Improving Financial Literacy and Saving Spirit of Muhammadiyah Perumnas Elementary School Students - Nurul Qalbi Insaniah; Siti Walida Mustamin; Safitri Nurfianti; Lutfi Andi Abrar; Nurul Amira Hasmin; Muh. Syukrianza; Andi Muh. Ghazi Alghifari; Marwan; Muh. Wahyu Iskandar; Salman Al Farizy; Muh. Ilham Syamsur (www.amertainstitute.com, 2025)
Financial literacy is a fundamental life skill that needs to be introduced from an early age to foster responsible financial behavior. In Indonesia, the financial literacy index remains relatively low, particularly among children, which highlights the urgency of providing practical and engaging financial education at the elementary level. This community service program was designed to enhance the financial literacy and saving spirit of third-grade students at Muhammadiyah Perumnas Elementary School, Makassar. A total of 21 students participated in a two-hour interactive session employing a combination of lectures, evaluative quizzes, and the distribution of learning tools such as saving-target piggy banks. The educational content covered the definition of financial literacy, the concept and benefits of saving, distinguishing needs from wants, and simple saving methods. The findings revealed a significant improvement in students’ understanding of core financial concepts. The active participation and enthusiasm displayed by the students indicated that the methods used were effective in increasing awareness and encouraging positive financial habits. Furthermore, the program successfully instilled motivation for saving by providing tangible tools that supported daily practice. These results suggest that financial education at the primary school level can lay a strong foundation for long-term financial responsibility and independence. Broader implementation of similar initiatives is recommended to support national efforts in improving financial literacy and to prepare younger generations for future economic challenges.